(untitled) (Czech Journal of International Relations, 1997)
A relatively significant decline can be observed in the Czech journalism of the interest in Eastern European issues, both in the field of political science and sociology. On the one hand, it is understandable after a long period, in Germany this issue was a priority, however, on the other hand, this trend does not correspond to reality, because the problems of Eastern Europe, especially Russia and the former Soviet republics, cannot remain without influencing the situation of the whole of Europe and in the case of republics located in a non-European geographical area, also in other areas. Economic, security, demographic and social problems abound certainly a reflection on its equivalents in the last parts of Europe and the entire continent. You can’t therefore approach them from the position of "hic sunt leones", but it is necessary to pay serious attention to them in the necessary scope and intensity.